Robust PID×(n-2) stage PD cascade controller - Kitti, Tirasesth; Jongkol, Ngamwiwit; Prasit, Julsereewong; Thanit, Trisuwannawat; Michihiko, Iida (My University, 1999)
This paper presents a design technique for the two degree of freedom (2-DOF) control system using PID (Proportional-Integral-Derivative)×(n-2) stage PD as a cascade controller for a class of nth order plant. It is intended to satisfy both transient and steady state response specifications based on the root locus approach. This controller can be used instead of the conventional PID controller for the higher order plant to obtain better performance. The transfer function of a class of nth order plant should not include zeros, the poles of the plant should have negative real part. The overall system is approximated as a stable and robust second order system. The performances of the controlled system are satisfied by this design technique. Moreover, this technique can also be applied to the plant with small dead time. The cascade controller gain can be adjusted to meet faster responses with a little or no overshoot. Robustness properties given by this controller proposed in this paper have also been demonstrated by numerical examples.